Identifikasi Bahan Tambahan Pangan yang Berbahaya (Rhodamin B dan Borak) pada Jajanan di Lingkungan Jl. Kartini Kecamatan Tegal Timur Kota Tegal - Adevia Maulidya Chikmah; Iroma Maulida (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
School children are state assets as human resources for the success of nation building. However, elementary school children are also one of the nutritionally vulnerable groups due to the need for macronutrient nutrients such as energy, protein, fat and other nutrients for the growth and development of bones, teeth, muscles and blood[9] . Breakfast habits need to be considered to provide energy for the body and so that children are more receptive to learning. But children have a lot of activity so they often forget to eat. 1 Snack is often an alternative for children who have not had breakfast. There are several types of food additives that are dangerous if mixed in snacks, including rhodamine B and borax. Research is intended to identify the presence of hazardous food additives, namely Rhodamin B and borax in snacks in the neighborhood of Jl. Kartini East Tegal District, Tegal City in 2017. This research is descriptive with a population that is snacks that do not have food labels sold along Kartini Street, Tegal City which looks chewy for snacks containing borax and bright red / striking for snacks containing rhodamine B. The number of samples we examined were 31 snacks consisting of 22 snacks as borak samples and 9 rhodamin B sample snacks. The test equipment was used Borax Kit and Rhodamin Kit. The results showed that there were 7 (31.8%) borax-containing snacks and 3 (33.3%) containing rhodamine B. In this study the factors of education, socio-economic, knowledge and attitudes of traders were not examined. Therefore, it is necessary to further examine the factors of education, socio-economics, knowledge and attitudes of traders towards preservatives at risk. Keywords— Borax, Rhodamin B, Additive Substance